EVALUASI PENGARUH KETERSEDIAAN JARINGAN LISTRIK PT. PLN (PERSERO) RAYON BOMBANATERHADAP PERKEMBANGAN PERUMAHANDI KECAMATAN RUMBIA - Sukardi Sukardi; Mustarum Musaruddin; Eng. Lukas Kano Manggalla (Jurnal Perencanaan Wilayah, 2017)
Evaluation of Availability of Electricity Network PT. PLN Rayon Bombana on the development of Housing in Kecamatan Rumbia, Sukardi / G2F1 15 036, Study Program of Regional Development Planning, Post Graduate, Haluoleo University, Supervised I: Mustarum Musaruddin, ST., MIT., Ph.D, and Supervised I II: Dr. Eng. Lukas Kano Manggalla, ST., MT. This study aims: 1) To determine the comparison between the amount of electricity costs with the level of service officer PT. PLN Rayon Bombana, 2) To know the influence of service level, the amount of electricity cost, and Housing Condition on Electricity consumption usage, 3) To know how far the influence of housing on the availability of Electrical Energy?. The use of Electricity Energy Consumption, the amount of electricity cost, Housing Condition and Service Level of PLN Officer become the variable in this research. This research was conducted by field observation / survey technique, questionnaire division and direct interview to related stockholder. The data were then analyzed using Multiple Regression by witth (SPSS), the relationship between housing with electricity. Forecasts of residential electric power needs using DKL 3.2 model. From result of research got that cost, service level, housing condition to electric energy consumption obtained multiple linear regression equation Y = 7,773 - 0,161 (cost) + 0,610 (Service Level) + 0,183 (Housing Condition). From the equation, the greater the cost of electricity then the level of energy consumption decreases. The better the level of service the higher the consumption of electrical energy and the increasing the housing conditions then the consumption of electrical energy also increases. To anticipate the growth of electrical energy, it needs to be prepared allocation of investment cost of electricity development.Keywords: Housing, Electricity